Multinational comparison of new antidepressant use in older adults: a cohort study. Issue 5 (14th May 2019) - Tamblyn, Robyn; Bates, David Westfall; Buckeridge, David L; Dixon, Will; Forster, Alan J; Girard, Nadyne; Haas, Jennifer; Habib, Bettina; Kurteva, Siyana; Li, Jack; Sheppard, Therese
Abstract : Objectives: We used an international pharmacosurveillance network to estimate the rate and characteristics of antidepressant use in older adults in countries with more conservative (UK) and liberal depression guidelines (Canada, USA). Setting: Electronic health records and population-based administrative data from six jurisdictions in four countries (UK, Taiwan, USA and Canada). Participants: A historical cohort of older adults (≥65 years) who had a new episode of antidepressant use between 2009 and 2014. Outcome measures: The age and sex-standardised cumulative incidence of new episodes of antidepressant use in older adults was measured. Descriptive statistics were used to compare the proportion of new users by the antidepressant prescribed, therapeutic class, potential treatment indication and country, as well as the characteristics of the first treatment episode (standardised daily doses, duration and changes). Results: The incidence of antidepressant use between 2009 and 2014 varied from 4.7% (Montreal and Quebec City) to 18.6% (Taiwan). Tricyclic antidepressants (TCAs) were the most commonly used class in the UK (48.8%) and Taiwan (52.4%) compared with selective serotonin reuptake inhibitors (SSRIs) in North American jurisdictions (42.3%–53.3%). Chronic pain was the most common potential treatment indication (41.2%–68.2%). Among users with chronic pain, TCAs were used most frequently in the UK and Taiwan (55.2%–60.4%), whereas SSRIs were used most frequently in North America (33.5%–46.4%). Treatment was longer (252–525 vs 169–437 days), standardised doses were higher (0.7–1.3 vs 0.5–1.0) and treatment was more likely to be changed (31%–46% vs 21%–34%) among patients with depression (9.1%–43%) than those with chronic pain. Conclusion: Antidepressant use in older adults varied 24-fold by country, with the UK, which has the most conservative treatment guidelines, being among the lowest. Chronic pain was the most common potential treatment indication. Evaluation of real-world risks of TCAs is a priority for future research, given high rates of use and the potential for increased toxicity in older adults because of potent anticholinergic effects.